Impact of incentives system on motivation to improve employee performance in UAE public sector - Khamis Al Naqbi, Rashid Ahmed (2020)
UAE market is one of the most attractive market to employees because of the UAE lifestyle and the employment benefits. However, employee’s turnover is high in UAE private and public sector, which affects the overall employee performance. Starting form this gap, the aim of this study was to examine the effects of incentive system on the employee’s performance along with the mediating role of motivation in UAE organizations that could guide policy maker and practitioner to design and implement an efficient incentives system for the HR managers in public institutions. The conceptual frame of this particular study are dependent upon two theories; Maslow’s need hierarchy theory and incentive - performance theory. This study has proposed incentives system as independent variable, employee’s motivation as mediating variable, and employee’s performance as dependent variable in the UAE organizational context. The quantitative research approach has been used to study the relationship among variables and the data collected by a well-structured survey. This study has applied a cross-sectional survey method and the unit of analysis was the employees in public sector organizations operating in UAE. The employees working in the Sharjah Economic Development Department at UAE are chosen as population and out of them 428 are framed as the final sample for this study. The survey was conveyed to 310 employees’ individuals from “Sharjah Economic Development Department” but gathered 249 substantial questionnaires. Results shows that social intensives have the highest impact, followed by monetary invectives, then Non-Monetary on employees motivation and employees performance. In addition, the three relations have significant direct effects and significant indirect effects. Therefore the three mediating hypotheses is accepted with partial mediating effect. Results shows that employees need in the UAE market is upgraded to social incentives which is higher that monetary need and HRM managers should consider this fact while designing their systems.